Elite refereeing structures in England: a perfect model or a challenging invention?. (2nd January 2017) - Webb, Tom
Abstract : The structure employed in England for referees and elite referees is something which has evolved as the game of Association Football has developed over time. This referee promotion, support and management system has changed more rapidly since the inauguration of the Premier League and latterly since the introduction of 'full-time' or 'professional' referees. The change in the promotion and support for elite referees has necessitated changes to that management structure at the elite level in particular. This article has utilized historical research to analyse the changes to these structures alongside semi-structured interviews as a means of analysing this evolving network for elite referees. Findings indicate that support for the changes which have occurred in elite refereeing regarding the establishment of 'full-time' referees are opposed, with alternating views also encompassing the current structure employed for managing elite referees in England and the pathways utilized for referee promotion.